Performance analysis of a combined heat and compressed air energy storage system with packed bed unit and electrical heater. (5th November 2019) - Wang, Peizi; Zhao, Pan; Xu, Wenpan; Wang, Jiangfeng; Dai, Yiping
Highlights: A CH-CAES system with packed bed is proposed to expand storage energy/power levels. The component transient models are adopted to predict the transient behaviors. The thermodynamic analysis of first cycle and multiple cycles are carried out. Effect of power distribution ratio and electrical heating temperature is studied. Abstract: Electric energy storage techniques are imperative when integrating intermittent renewables to power system to conquer the mismatch between power generation and consumption. In order to expand the energy/power capacity of compressed air energy storage system (CAES) flexibly in a fixed cavern size condition, a combined heat and compressed air energy storage system (CH-CAES) with packed bed unit and electrical heater based on adiabatic concept is developed. In such a system, electricity is stored in the form of both thermal and pressure energies. In order to predict the system transient behaviors, the turbomachinery's off-design performance and 1D two-phase transient model of packed bed have been adopted. Firstly, the thermodynamic analysis in first cycle has been conducted. Results show that a system roundtrip efficiency of 58.86% can be achieved when the packed bed unit efficiency is 92.53%. Then, the variations of both system and component performances during multiple successive cycles are implemented. Both roundtrip efficiency and thermal energy storage efficiency increase with raised cycles. Links between components are discussed. The temperature distribution in packed bed varies in each cycle, leading to an improvement in high-pressure turbine inlet temperature and thus the change of turbine performance. Finally, the influence of power distribution ratio, electrical heating temperature and partial charging/discharging on system performance is discussed. System roundtrip efficiency increases with power distribution ratio but decreases with electrical heating temperature.